Reimagining Play Spaces: A Visual–Verbal Video Analysis of Children’s Spatial Behavior and Material Engagement in Early Learning Environments (Architecture Image Studies, 2025)
This study explores how recycled tyres as sustainable play materials influence the spatial behavior and developmental outcomes of preschool children. Drawing on Visual–Verbal Video Analysis (VVVA), the research investigates the dynamic interactions between children, materials, and space in two urban preschools in Accra, Ghana. Forty-five children aged 2–4 years were observed over a three-month period through video recordings, field notes, and photographic documentation. Using Nicholson’s Loose Parts Theory and spatial affordance principles, recycled tyres were introduced into play environments to encourage creativity, movement, and cooperative engagement. Data were analyzed through VVVA, integrating visual and verbal modalities to identify patterns across five play types—constructive, dramatic, physical, cooperative, and games with rules. Findings revealed that recycled tyres enhanced open-ended exploration, spatial coordination, and peer collaboration, fostering both cognitive and socio-emotional growth. The integration of VVVA themes and spatial dimensions (as summarized in Tables 1 and 2) demonstrated that material flexibility, spatial layout, and group interaction collectively shape children’s play experiences. The study contributes to early childhood and environmental design research by showing how sustainable materials can transform play spaces into inclusive, developmentally enriching environments. Implications for preschool design, sustainability education, and child-centered learning are discussed.